2019
DOI: 10.1371/journal.pcbi.1006685
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology reveals how altered TGFβ signalling with age reduces protection against pro-inflammatory stimuli

Abstract: Osteoarthritis (OA) is a degenerative condition caused by dysregulation of multiple molecular signalling pathways. Such dysregulation results in damage to cartilage, a smooth and protective tissue that enables low friction articulation of synovial joints. Matrix metalloproteinases (MMPs), especially MMP-13, are key enzymes in the cleavage of type II collagen which is a vital component for cartilage integrity. Transforming growth factor beta (TGFβ) can protect against pro-inflammatory cytokine-mediated MMP expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 92 publications
2
12
0
Order By: Relevance
“…Interestingly, in silico experiments with our model showed that blocking important transducers of inflammation such as the TGF-β-activating kinase (TAK1) or NFKB while activating the PTHrP related pathway could push a hypertrophic-like chondrocyte into transitioning towards a more healthy or anabolic state (Data file S2). Moreoever, other studies have reported that the TGF-β pathway had a protective effect against inflammation (28)(29)(30)(31), a scenario we evaluated with our model too. In silico mimicking the presence of inflammation in a healthy chondrocyte by forcing several inflammation related pathways of the model to be set at their highest values led to 100% of transition towards the diseased hypertrophic state (Fig.…”
Section: The Computational Model Successfully Recapitulated Two Chondrocyte Phenotypes and Physiologically Relevant Behaviorsmentioning
confidence: 98%
“…Interestingly, in silico experiments with our model showed that blocking important transducers of inflammation such as the TGF-β-activating kinase (TAK1) or NFKB while activating the PTHrP related pathway could push a hypertrophic-like chondrocyte into transitioning towards a more healthy or anabolic state (Data file S2). Moreoever, other studies have reported that the TGF-β pathway had a protective effect against inflammation (28)(29)(30)(31), a scenario we evaluated with our model too. In silico mimicking the presence of inflammation in a healthy chondrocyte by forcing several inflammation related pathways of the model to be set at their highest values led to 100% of transition towards the diseased hypertrophic state (Fig.…”
Section: The Computational Model Successfully Recapitulated Two Chondrocyte Phenotypes and Physiologically Relevant Behaviorsmentioning
confidence: 98%
“…However, TGF-β signalling has also been shown to be dysregulated in several age-associated diseases, including atherosclerosis, neurodegenerative diseases and arthritis, and is upregulated in tendon injury [ 64 , 65 ]. In cartilage, TGF-β switches from a protective to a detrimental role with ageing, which is associated with osteoarthritis development [66] . TGF-β has also been identified as a master regulator of fibrosis [67] , and it is therefore likely that dysregulation of TGF-β signalling in the old Achilles drives the increase in fibrosis-associated proteins within the IFM.…”
Section: Discussionmentioning
confidence: 99%
“…However, TGF-β signalling has also been shown to be dysregulated in several age-associated diseases, including atherosclerosis, neurodegenerative diseases and arthritis, and is upregulated in tendon injury,[46, 47]. In cartilage, TGF-β switches from a protective to a detrimental role with ageing, which is associated with osteoarthritis development,[48]. It is possible that dysregulation of TGF-β signalling in the old Achilles drives the changes in the IFM proteome that we report here.…”
Section: Discussionmentioning
confidence: 99%